Program Usaha Kesehatan Sekolah di Masa Pandemi: Antara Harapan dan Kenyataan - Nurochim Nurochim; Siti Ngaisah (Universitas Pendidikan Indonesia, 2021)
The purpose of this study is to describe school-based health education. This study was conducted using a qualitative method of literature review. The results of the study show health education as a potential program in non-natural disasters covid19. School-based health programs consist of health education activities, health services, and healthy environmental development. This activity is an effort to create a clean and healthy lifestyle. Clean and healthy living habits as an effort to reduce the spread of the virus which is increasingly widespread. However, the implementation of school-based health activities was not carried out optimally and experienced various obstacles. The obstacles to implementing school-based health are lack of funds, competence in human resources, and inadequate facilities and infrastructure.